Gestión por competencias para el fortalecimiento del desempeño del talento humano del Distrito de Educación 13D07 Chone-Flavio Alfaro - Bermúdez Palomeque, Marcos Alejandro (2022)
The objective of this research is to propose a competency-based management model to strengthen the performance of human talent in the District of Education 13d07 Chone - Flavio Alfaro in the province of Manabí. It is important to identify the competencies of each process, to strengthen the performance of human talent. The methodology used in this study is non-experimental, with an inductive, bibliographic method, techniques such as the interview with the director of the district human talent unit, the survey of 59 public officials. Direct observation was applied through a process verification sheet, SWOT analysis, cross-impact matrix. As a result, a diagnosis of the current situation of human talent management was developed. In addition, a dictionary of skills was developed for the analysis and description of jobs using the DACUM matrix. As a conclusion, the proposal of a competency-based management model that strengthens human talent was developed, the following steps were established according to the needs of the institution: recruitment, qualification, qualification, empowerment, definition of structures and profiles.